Nasal sequelae of Treacher Collins syndrome. Issue 6 (June 2015) - Plomp, Raul G.; Mathijssen, Irene M.J.; Moolenburgh, Sanne E.; van Montfort, Kees A.G.M.; van der Meulen, Jacques J.N.M.; Poublon, René M.L.
Summary: Objective: This study aimed to determine external and endonasal deformity, and satisfaction with nasal functioning and appearance, in Treacher Collins syndrome. Study design: A cross-sectional cohort study was conducted. Methods: Eleven adult patients with Treacher Collins syndrome were compared with 151 controls in terms of satisfaction with nasal functioning and appearance by means of the Nasal Appearance and Function Evaluation Questionnaire. In all patients with Treacher Collins syndrome, external nasal deformities were scored on standardized digital photographs of the nose as rated independently by three experienced physicians. Endonasal deformity was determined by standardized nasal endoscopy. Results: The patients were relatively satisfied with the various esthetic nasal subunits. The most significant functional problems were snoring ( P = 0.001) and quality of phonation ( P = 0.003). The main external nasal deformities were the dorsal hump (73%), external deviation (≤55%), the bifid or bulbous nasal tip (55%), and columellar septal luxation (55%). In 82% of the patients, a septal deviation was found, often associated with spurs. Conclusion: Satisfaction with esthetics of the nose was fair, but these patients suffer from the functional problems of snoring and impaired quality of phonation. A structured nasal ENT physical examination with nasal endoscopy might determine aspects requiring more attention during treatment. Septorhinoplasty can be performed at an adult age if there is a considerable esthetic wish of the patient and/or nasal obstruction combined with septal deviation. Attention should be paid to dorsal hump reduction, correction of the deviated external osseous framework, septoplasty, and correction of the nasal tip shape. Level of evidence :2b